The influence of online audios on listening comprehension for efl a1 learners in a high school of Riobamba - Silva Verdezoto, Jaime Ramiro (2021)
This study was conducted to help students improve their listening comprehension with the aid of online audios. Participants were 10th graders from a public high school located in Riobamba. They were divided into two groups. One was the experimental group and the other the control group. A mixed-design study was carried out. Quantitative and qualitative data was gathered with instruments like pretest and posttest, surveys, interviews, and learning logs. Findings report that both groups (experimental and control) had very low results in the pretest. However, posttests results determined that the experimental group outperformed the control one. Students’ perspectives towards listening in English changed from difficult to easy. They attributed the positive changes to the teacher’s help and the practice they had with online audios. Among the difficulties, students mentioned that it was difficult to differentiate it was a name or a word in English, and that it was difficult to identify the accent. These difficulties were reduced with the intervention. Therefore, they suggest including online audios in regular English classes. Implications of these findings involve other teachers of English as a foreign language (EFL) who like to improve their students’ listening comprehension.